STUDENTS’ LEARNING READINESS FROM KINDERGARTEN TO PRIMARY SCHOOL - Hernik Farisia; Tatik Mukhoyyaroh (Universitas Majalengka, 2025)
Building children's readiness for learning during the transition from Early Childhood Education (ECE) to Elementary School (ES) will help children adapt to the new school environment and will influence their subsequent learning process. This study aims to (1) analyze children's learning readiness from a psychological perspective, and (2) to identify effective strategies to support their transition from early childhood education to elementary school. This qualitative research employed interviews and observations of three early childhood participants (ages 6-8) identified as having high (NA), medium (RA), and low (RD) learning readiness based on indirect questionnaires from 19 first-grade students. The secondary data were obtained from two classroom teachers and the school principal. This study utilized source triangulation (participants, parents, and teachers), technique triangulation (observation and interviews), and time triangulation. The findings indicate that the aspects of physical development and health, approaches to learning, cognition and general knowledge, language and early literacy, and social and emotional development vary among the three respondents. Effective strategies applied to respond to children's learning readiness is focusing on improving the quality of learning by aligning the concepts of early elementary school learning with those of ECE through enjoyable learning processes, instructional adjustments, and parental involvement in the ECE-ES transition. This study provides insights for parents, teachers, and educators in preparing children for the transition, emphasizing cognitive aspects, physical, and socio-emotional aspects. Additionally, recommendations are made for schools regarding the provision of enjoyable learning experiences for students, facilitate teaching at the right level, and ensuring students are well-prepared for subsequent stages of learning through parent involvement.